2005
DOI: 10.1111/j.1600-0404.2004.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced external counterpulsation does not compromise cerebral autoregulation

Abstract: Stable gain and phase values suggest that EECP does not compromise CA and, therefore, does not seem to bear cerebrovascular risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Regulation of downstream resistance may be one of several possible mechanisms to preserve a stable cerebral perfusion in response to diastolic augmentation in the MCA. Marthol et al [19] provided evidence that CA is preserved during ECP in healthy subjects using dynamic CA measurements. Here, the regulation of downstream resistance may be one of several possible mechanisms to preserve a stable cerebral perfusion in response to diastolic augmentation in the MCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of downstream resistance may be one of several possible mechanisms to preserve a stable cerebral perfusion in response to diastolic augmentation in the MCA. Marthol et al [19] provided evidence that CA is preserved during ECP in healthy subjects using dynamic CA measurements. Here, the regulation of downstream resistance may be one of several possible mechanisms to preserve a stable cerebral perfusion in response to diastolic augmentation in the MCA.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data on the mechanisms and effects of ECP-induced diastolic flow augmentation on cerebrovascular resistance. Marthol et al [19] assessed the influence of brief ECP on dynamic CA. They found that ECP does not compromise CA in 23 healthy and 12 atherosclerotic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…After optimising the Doppler signal, the probe was attached to the skull at a fixed angle using a headband with an adjustable positioning system. Respiratory frequency was monitored by means of inductance plethysmography using two calibrated belts attached around the thorax and abdomen (Respitrace Calibrator; Ambulatory Monitoring, Ardsley, NY, USA) [13].…”
Section: Methodsmentioning
confidence: 99%
“…In our case series, there was no increase in intravascular peripheral resistance during the IABI procedure. This could imply greater antegrade flow induced by the device without increase of downstream resistance 20,21 …”
Section: Discussionmentioning
confidence: 99%